MIGRASI INTERNASIONAL DAN PEMERIKSAAN KEIMIGRASIAN DI INDONESIA PASCA PANDEMI COVID-19: KEBIJAKAN IMIGRASI RESTRIKTIF, PROAKTIF, DAN SELEKTIF - Arikson, Arikson; Sholehah, Fithaloka Hartinawati; Syahputra, Rino Rahaditya; Rochman, Pekik Aulia; Ilyandi, Rendy (Jurnal Ilmiah Kajian Keimigrasian, 2024)
This research aims to analyse the impact of post-Covid-19 migration policies in Indonesia, focusing on restrictive, proactive, and selective policies. Through a mixed approach combining quantitative and qualitative analyses, this research aims to provide a holistic and in-depth understanding of the impact of migration policies on international population movements, the contribution of migrants to economic recovery, as well as the dynamics of migrant selection and their integration across different sectors and regions in Indonesia. The results of this research are expected to provide critical insights to policymakers to formulate migration policies that are in accordance with the actual conditions and needs of society. In addition, this study will also help in understanding the contribution of migrants to economic recovery, paying attention to the social and economic impacts of proactive policies implemented. The study also provides a foundation for the protection of migrant workers' rights and sustainable national economic recovery strategies. Finally, the study considers the changing views of society towards migration, enabling the identification of factors that influence perceptions and enhancing understanding of social integration amidst new post-Covid-19 migration policies.